Fingerprint analysis laboratory workbook - Daluz, Hillary Moses (Milton : Chapman & Hall/CRC Press, 2018)
Fingerprint collection and analysis may be performed as part of many jobs, including crime scene technician, latent print examiner, criminalist, and lab supervisor. Regardless of one's specific background or role in the process, a knowledge of scientific practices is critical in handling and analyzing fingerprint evidence. The best way to understand the principles and concepts of any science learned in a classroom is to perform experiments. The exercises in Fingerprint Analysis Laboratory Workbook, Second Edition address all aspects of fingerprint theory, investigation, processing, comparisons, and research. Designed specifically to parallel the Fundamentals of Fingerprint Analysis, Second Edition textbook, the laboratory exercises correspond with the textbook chapters, with exercise in the lab chapter putting into practice the concepts covered in the text chapter. Each lab follows the same format, beginning with the objectives of the experiment and providing the background information necessary to perform the experiment. This is followed by a list of required materials, the lab exercises, and post-lab questions for students to test what they've learned. Many of the laboratory exercises may be completed either at home or in a laboratory setting. Exercises and photographs enhance the text, making it an ideal hands-on learning tool. New techniques and current practices added to the primary textbook have been included in this companion laboratory workbook to cover the latest in real-world application of fingerprint analysis science to practice.
Chapter 9. Forensic Light Sources9.1 Background; 9.2 Materials; 9.3 Exercises; Part I: Fluorescent Fingerprint Powder; Part II: Observing Fluorescence; 9.4 Post-Lab Questions; Chapter 10. Physical Processing Methods; 10.1 Background; 10.2 Materials; 10.3 Exercises; Part I: Black and Bi-Chromatic Fingerprint Powders; Part II: Magnetic Fingerprint Powder and Casting Material; 10.4 Post-Lab Questions; Chapter 11. Chemical Processing Methods: Porous Substrates; 11.1 Background; 11.2 Materials; 11.3 Exercises; Part I: 1, 2 -Indanedione; Part II: DFO; Part III: Ninhydrin; 11.4 Post-Lab Questions.
Chapter 14. Documentation.
OCLC-licensed vendor bibliographic record.
Keywords: Fingerprints; Fingerprints -- Identification; Forensic sciences; Criminal investigation; LAW -- Forensic Science; LAW -- Criminal Law -- General